2010
DOI: 10.1099/ijs.0.019695-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and delineation of phytoplasmas based on secY gene sequences

Abstract: The secY gene sequence is more variable than that of the 16S rRNA gene. Comparative phylogenetic analyses with 16S rRNA and secY gene sequences from 80 and 83 phytoplasma strains, respectively, were performed to assess the efficacy of these sequences for delineating phytoplasma strains within each 16Sr group. The phylogenetic interrelatedness among phytoplasma taxa inferred by secY gene-based phylogeny was nearly congruent with that inferred by 16S rRNA gene-based phylogeny. Phylogenetic analysis based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 37 publications
1
79
0
1
Order By: Relevance
“…Nucleotide sequence analyses revealed that the amplicons each contained a partial (39-end) rpl15 ribosomal protein (rp) gene, a complete secY gene, and a partial (59-end) map (methionine aminopeptidase) gene. Like various group 16SrIII phytoplasma strains and unlike some other phytoplasmas (Lee et al, 2010), the X-disease phytoplasma strains in this study lacked an adk (adenylate kinase) gene between the secY and map genes, a feature that marks a major evolutionary divergence among phytoplasma subclades. A 9-base insertion/deletion (indel) in the secY genomic locus distinguished two group 16SrIII phytoplasma strain clusters, one group containing strains having a secY gene length of 1263 bases (strains PX11CT1 R , PX11CT2, PX92CT1, PX92CT4, CX-95, WX95, WWB, PoiBI, SP1), and the other group containing strains having secY length of 1272 bases (strains CYE, MW1, GR1, PBT, PPTAKpot6, PPTAKpot7, PPTMT117, VAC) (Fig.…”
Section: Description Of 'Candidatus Phytoplasma Pruni'mentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleotide sequence analyses revealed that the amplicons each contained a partial (39-end) rpl15 ribosomal protein (rp) gene, a complete secY gene, and a partial (59-end) map (methionine aminopeptidase) gene. Like various group 16SrIII phytoplasma strains and unlike some other phytoplasmas (Lee et al, 2010), the X-disease phytoplasma strains in this study lacked an adk (adenylate kinase) gene between the secY and map genes, a feature that marks a major evolutionary divergence among phytoplasma subclades. A 9-base insertion/deletion (indel) in the secY genomic locus distinguished two group 16SrIII phytoplasma strain clusters, one group containing strains having a secY gene length of 1263 bases (strains PX11CT1 R , PX11CT2, PX92CT1, PX92CT4, CX-95, WX95, WWB, PoiBI, SP1), and the other group containing strains having secY length of 1272 bases (strains CYE, MW1, GR1, PBT, PPTAKpot6, PPTAKpot7, PPTMT117, VAC) (Fig.…”
Section: Description Of 'Candidatus Phytoplasma Pruni'mentioning
confidence: 99%
“…We also provide data on two additional genomic loci for the designated 'Ca. Phytoplasma pruni' reference strain PX11CT1 R , as well as for other strains, since improved delineation of species should be achieved through analyses of more variable gene sequences (Lee et al, 2010;Martini et al, 2007). Availability of nucleotide sequences from multiple genetic loci, such as those encoding SecY and ribosomal proteins, especially for the reference strain of a 'Ca.…”
Section: Description Of 'Candidatus Phytoplasma Pruni'mentioning
confidence: 99%
See 1 more Smart Citation
“…PCR conditions and primers were as described by Gundersen et al (1996), Langer & Maixner (2004), Martini et al (2007) and Lee et al (2010). PCRproducts were cloned in plasmid vector pCRII-TOPO (Invitrogen) and propagated in Escherichia coli.…”
mentioning
confidence: 99%
“…Recently, other ribosomal and protein-encoding genes have been used to improve phytoplasma strain differentiation and/or to develop diagnostic methods (Lee et al 2010;Davis et al 2013;Dumonceaux et al 2014). The Cpn60-encoding gene has been successfully used as a marker for phytoplasma detection and differentiation (Mitrović et al 2011;Sugawara et al 2012;Alvarez et al 2014), and an approximately 550 bp portion of this gene, known as the chaperonin 60 universal target (cpn60UT) (Goh et al 1996) can be universally accessed and used to differentiate phytoplasmas (Pérez-López et al 2014;Dumonceaux et al 2014).…”
Section: Introductionmentioning
confidence: 99%